DIGITAL PLATFORMS AS MECHANISMS FOR EMPLOYER ENGAGEMENT IN VOCATIONAL EDUCATION - Sodiqova Gulnora Ergashaliyevna (International Scientific and Current Research Conferences, 2025)
This article explores the transformative potential of digital platforms in facilitating employer participation within vocational education systems. As labor markets increasingly demand agile, competency-based, and industry-aligned skill sets, traditional mechanisms of employer engagement often prove insufficient. Digital platforms offer a multi-faceted solution, providing interactive spaces for real-time collaboration, curriculum co-development, apprenticeship management, and labor market analytics. The study synthesizes current theoretical frameworks, evaluates contemporary case studies, and interrogates the efficacy of digital interfaces in bridging the gap between vocational institutions and industry stakeholders. Furthermore, it elucidates the challenges of platform adoption, including technological readiness, stakeholder resistance, and data security concerns, highlighting the conditions under which digital mechanisms can optimize workforce preparedness and vocational learning outcomes.